ANALISIS KESULITAN MEMBACA PERMULAAN SISWA KELAS 1 SDN HABAU HULU KECAMATAN BANUA LAWAS KABUPATEN TABALONG - Azizah, Nor; Winindyasari Palupi, Tri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Early reading is a fundamental skill that elementary school students must master as a basis for understanding various learning materials. However, in practice, some students still experience reading difficulties, which affects the classroom learning process. This study aims to describe the forms of early reading difficulties and analyze the factors influencing these difficulties among first-grade students at SDN Habau Hulu, Banua Lawas District, Tabalong Regency. The study employs a qualitative approach using a descriptive method. The research subjects consisted of one first-grade teacher and five students selected via purposive sampling based on the severity of their reading difficulties. Data were collected through observation, interviews, and documentation, then analyzed using the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the forms of early reading difficulties include an inability to recognize letters with similar shapes, difficulty spelling syllables, an inability to combine syllables into meaningful words, mispronunciation of certain letter sounds, and a tendency to guess words without paying attention to the full sequence of letters. The factors influencing these difficulties comprise both internal and external factors. Internal factors include low concentration, easily distracted attention, a tendency to get bored quickly, and anxiety when reading in front of peers. Meanwhile, external factors include a lack of parental guidance in fostering reading habits at home, limited time for family study sessions due to work commitments, and high levels of gadget usage, which reduce students' interest in and time for practicing reading. These findings suggest that addressing early reading difficulties requires collaboration among teachers, parents, and the learning environment to ensure students' reading skills develop optimally.